2021
DOI: 10.1016/j.ijwd.2020.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Bridging racial differences in the clinical encounter: How implicit bias and stereotype threat contribute to health care disparities in the dermatology clinic

Abstract: Background Positive interactions that build good relationships between patients and providers demonstrate improved health outcomes for patients. Yet, racial minority patients may not be on an equal footing in having positive interactions. Stereotype threat and implicit bias in clinical medicine negatively affect the quality of care that racial minorities receive. Dermatology, one of the least racially diverse specialties in medicine, further falls short in providing patients with options for race-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Inviting your patient’s input is an essential component to implementing active communication skills that foster the development of a healthy patient-doctor relationship. 19 Herein, we present practical interventions that can be used when diagnosing skin of color patients with AD based upon prior successful clinical experiences and a review of the literature.…”
Section: Practical Interventions: Look Listen Feelmentioning
confidence: 99%
“…Inviting your patient’s input is an essential component to implementing active communication skills that foster the development of a healthy patient-doctor relationship. 19 Herein, we present practical interventions that can be used when diagnosing skin of color patients with AD based upon prior successful clinical experiences and a review of the literature.…”
Section: Practical Interventions: Look Listen Feelmentioning
confidence: 99%
“…Studies have shown that healthcare workers may hold conscious and unconscious negative stereotypes of non‐White patients 13 . Strategies to reduce implicit bias include using a more diverse provider group to reflect that of the population (more non‐White dermatologists) and investing in workforce diversity, equity, and inclusion 14 . In addition, metacognition should be harnessed when taking a history to ensure one is not inappropriately stereotyping the patient (see Table 1).…”
Section: Categorizing Cognitive Biases In Dermatology By Each Stage O...mentioning
confidence: 99%
“…For example, research has shown that negative stereotypes among physicians may affect the care received by non-White patients. 17 These implicit biases also occur in dermatology, [18][19][20] and may manifest as less time spent with patients, less positive interactions, and less patient understanding of the care that is provided. 18,21,22 Increasing diversity within the dermatology workforce, improving clinical education, and increasing awareness of implicit biases by promoting an environment of cultural competence should lessen the unconscious reliance on stereotypes and improve dermatologic care of SOC patients.…”
Section: Why Is This Important? Implications For Patient Carementioning
confidence: 99%